The Prevalence of CTX-M-15 Extended-spectrum β-Lactamases Among Salmonella spp. and Shigella spp. Isolated from three Iranian Hospitals - Bialvaei, Abed Zahedi (Eur J Microbiol Immunol (Bp), 2017)
Bacterial antimicrobial resistance mediated by the production of extended-spectrum β-lactamases (ESBLs) is considered a major threat for treatment of Salmonella and Shigella infections. This study aimed to investigate antibiotic resistance patterns of Salmonella and Shigella spp. and presence of CTX-M from three teaching hospitals in Iran. In the present study, 58 clinical Shigella and 91 Salmonella isolates were recovered between 2009 and 2013 from 3 teaching hospitals in Iran. After culture and antimicrobial susceptibility testing, ESBL-positive isolates were subjected to further investigations. These included polymerase chain reaction (PCR) amplification and DNA sequencing of bla(CTX-M-15) encoding plasmid. In both genera, high sensitivity to gentamicin and amikacin, but high resistance to ampicillin, tetracycline, and trimethoprim–sulfamethoxazole, was found. Molecular investigation showed that 31.8% isolates of Salmonella spp. and 34.48% isolates of Shigella spp. were CTX-M positive and all of them were also positive for ISEcpI. Protein translation, comparing with reference sequences, showed that all CTX-M isolates belong to CTX-M-15. The present study suggests that the resistance of ESBLs-producing Salmonella and Shigella spp. in Iran hospitals is very serious. Therefore, strategies to minimize the spread of ESBL-producing isolates should be implemented.